Enhanced pollution monitoring system for vehicles using cloud based wireless sensor network - Karthikeyan, P.; Aishwarya, M.; Swatha, M.; Bharathi, B.; Sivambiga, 5P. (International Journal of Psychosocial Rehabilitation, 2020)
Pollution has been put out by rapid growth in population, industrialization and higher levels of energy utilization. Air pollution has a significant influence on the concentration of constituents in the atmosphere directing to effects like global warming and avid rains. They also produce harmful effects on humans. To avoid such adverse imbalances in nature, air pollution monitoring system is most important. WSN is a network of devices that can communicate the information collected from a monitored field through wireless links. Data collected from the sensors can be transferred through multiple nodes via gateway. These networks can be used in monitoring the concentration of CO2 from the vehicle exhaust. WSN are used in monitoring pollution level at both indoors and outdoors. WSN have also been implemented in predicting forest fires in advance by sensing the level of CO2 emitted by trees and the moisture in the surrounding. In all these implementations, a network of sensors is used with few nodes acting as intermediary while others collecting data. Data collected is transferred to the sink node using an efficient algorithm.